1996
DOI: 10.1111/j.1467-2494.1996.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vichy water on catalase activity in the stratum corneum

Abstract: Synopsis Vichy spa water is essentially known for its therapeutic action on liver and bile duct functions. Its mechanism of action may be partially explained by the activation of certain digestive enzymes. A literature survey showed that Vichy water has also been used for local application in the treatment of certain dermatoses. Based on these data, the effects of Vichy spa water on the skin were studied using cutaneous enzymatic systems. The first studies were carried out on catalase, an oxidoreductase. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…3 Mineral 89 (M89, Laboratoires Vichy) contains 89% Vichy mineralizing water (VMW) as a hydrating agent and 0.4% hyaluronic acid (HA); an extracellular matrix component with viscoelastic and hygroscopic properties is able to control diverse cell processes and transepidermal water loss. 9 These primary antioxidant enzymes convert 2 potentially harmful reactive oxygen species, superoxide and hydrogen peroxide, to water. [4][5][6][7][8] In vitro and in vivo studies showed that VMW induced a statistically significant increase (P < .05) in the catalase enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Mineral 89 (M89, Laboratoires Vichy) contains 89% Vichy mineralizing water (VMW) as a hydrating agent and 0.4% hyaluronic acid (HA); an extracellular matrix component with viscoelastic and hygroscopic properties is able to control diverse cell processes and transepidermal water loss. 9 These primary antioxidant enzymes convert 2 potentially harmful reactive oxygen species, superoxide and hydrogen peroxide, to water. [4][5][6][7][8] In vitro and in vivo studies showed that VMW induced a statistically significant increase (P < .05) in the catalase enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In vitro and in vivo studies showed that VMW induced a statistically significant increase (P < .05) in the catalase enzyme activity. 9 These primary antioxidant enzymes convert 2 potentially harmful reactive oxygen species, superoxide and hydrogen peroxide, to water. 5,10 It has also shown to have anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, prevention of radical species production (NQO1), activation of the thioredoxin system (TXNRD1) (one of the major antioxidant defense systems) linked to peroxyredoxines’ activation (PRDX1,2,3 and 6) , reduction (GPX2) and dismutation of H 2 O 2 (CAT) are potentially activated in keratinocyte response to VTSW. Of note, the activation of catalase (CAT) was previously measured in the stratum corneum, after in vivo application of VTSW to human skin . However, considering the weak induction of in vitro CAT gene expression (not confirmed by qRT/PCR, Table ), this in vivo CAT activation by VTSW was more likely linked to the VTSW high hydrogenocarbonate content and buffering effect around pH 7.0.…”
Section: Discussionmentioning
confidence: 98%
“…Among these, prevention of radical species production (NQO1), activation of the thioredoxin system (TXNRD1) (one of the major antioxidant defense systems) linked to peroxyredoxines' activation (PRDX1,2,3 and 6) [67], reduction (GPX2) and dismutation of H 2 O 2 (CAT) are potentially activated in keratinocyte response to VTSW. Of note, the activation of catalase (CAT) was previously measured in the stratum corneum, after in vivo application of VTSW to human skin [30].…”
Section: Vtsw and Response To Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation